THE SOCIAL COGNITION´S IMPACT ON VOCATIONAL BEHAVIOR OF CARE STAFF FOR PEOPLE WITH DISABILITIES - José María Benavent Estrada (Universidad Nacional del Nordeste, 2020)
In recent years, numerous theoretical models based on the theory of empathy and self-efficacy founded the explanation of vocational behavior. The finding of a particular profile of the social cognition function in the staff that attends for people with disabilities makes it necessary to evaluate the dimension of their influence for inclusion in the evaluation of vocational behavior. The present work is a cross-sectional correlational quantitative type study for which a study group of 115 subjects of both sexes and a control group of 30 subjects with similar activities but without attention to people with disabilities were selected. The test used for the work were a sociodemographic questionnaire, emphatizing and systemizing test, modified coping strategies scale, reading the mind in the eyes test, temperament inventory and revised character of cloninger, faux pastest and scale of general self-efficacy. A particular profile of social cognitive function was found in the population that works in the field of care for people with disabilities, with significant differences defined by very high levels of cognitive (empathizing) and emotional empathy, high levels of systemizing and high results in variable cooperation and a direct relationship in the decrease in the ability to recognize hostile glances in the gaze test. These special characteristics are not explained or achieved only by the concepts of self-efficacy or empathy, so the study of social cognition function should be included in all studies of vocational behavior and professional development.